Sands of Iwo Jima - Dwan, Allan, 1885-1981; Wayne, John, 1907-1979; Agar, John, 1921-2002; Mara, Adele, 1923-2010; Tucker, Forrest, 1919-1986; Republic Pictures Corporation; Republic Entertainment Inc (Los Angeles, CA : Republic Entertainment, Inc. : Distributed by Artisan Home Entertainment, 2000)
Stryker (Wayne), a hard-nosed Marine sergeant prepares a company of recruits for combat in World War II's Pacific Theater. The new unit's training is soon put to the test in a full-scale battle against the Japanese on Iwo Jima. The famous flag-raising on Mt. Suribachi is depicted near the film's conclusion
"Catalog no. 55570."
Videodisc release of a 1949 motion picture
Contains the documentary, "The making of Sands of Iwo Jima."
Story, Harry Brown; camera, Reggie Lanning; editor, Richard L. Van Enger; music, Victor Young
John Wayne (Sgt. Stryker), John Agar (Pfc. Conway), Adele Mara (Allison Bromley), Forrest Tucker (Corp. Thomas)
DVD; Dolby Digital
Keywords: Marines -- United States -- Drama; Iwo Jima, Battle of, Japan, 1945 -- Drama; World War, 1939-1945 -- Drama; Feature films; War films; DVD-Video discs; Video recordings